Baseball player running to second base, Final game in Military Athletic Tournament, Alaska-Yukon-Pacific-Exposition, Seattle, Washington, 1909 - Nowell, Frank H., 1864-1950 (1909)
Orville J. Rognon started as a photographer in 1908 at Webster and Steven and in 1911 became a partner with Frank Nowell. Rognon moved to Vancouver, B.C. in 1913 and worked at the Canadian Photo Company. He then formed a partnership with Leonard Frank in 1918 to create the Commercial Photo Company. Rognon was probably hired by Frank Nowell, the official photographer for the Exposition. Caption on verso: R190. "Safe on Second" in the final baseball game of the tourney between the victorious navy team and the 14th Cavalry Team. PH Coll 779.17 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number